Analysis of Database Services for Cloud (International Journal of Engineering and Computer Science, 2017)
Cloud Computing can be described in terms of services which is being provided to users “pay as you go”. As a new technical field cloud is gaining attention due to continuous growth . With the help of internet, data and resources are shared between machines . As with cloud computing , if database services are being provided through it , then it can be called as Cloud Database . Nowadays DBaaS is upcoming new service in cloud computing scenario because more and more people now wish to save database work to cloud as they are affordable on low cost.